Eficiência nutricional ao fósforo de clones de batata - Sausen, Darlene (2016)
The potato plant is highly demanding regarding the presence of phosphorus (P) readily available in soil solution. To achieve high yields of tubers, large applications of phosphate fertilizers are made, which consequently reduce the sustainability of the potato chain and cause possible environmental contamination. Therefore, it is necessary to improve the management of fertilizer use and develop potato clones that have high yield and quality, even in limiting conditions of P. In order to identify efficient clones in P acquisition and use, this study aimed to characterize the physiological aspects of potato clones under different levels of P availability and production systems available. In the first experiment, the Asterix, Atlantic, SMIC 148-A and SMINIA 793101-3 clones from micropropagated plants were grown in soilless system under low and high P level (2.32 and 23.2 mg P L-1) during the spring and autumn seasons of Rio Grande do Sul state. In the P utilization efficiency, we found that the potato clones differ between the spring and autumn season of Rio Grande in soilless culture system with the use of sand as substrate. Furthermore, we also compared the P efficiency of these clones between soilless system and field cultivation under low and high P level (70 and 560 kg P2O5 ha-1) in the spring crop. We observed that each clone responds differently to cultivation systems used as nutritional efficiency to P, and the closed cultivation soilless system with use of sand as substrate overestimates the responses of potato clones in relation to P availability. Nevertheless, we sought to differentiate micropropagated potato plants of plants produced from minitubers as nutritional efficiency to P in closed cultivation soilless system with use of sand as substrate under high and low P level again. The data suggest that the propagative origin of the potato plants interferes, in the biomass ratio between root and shoot, and in the harvest index and P utilization efficiency for all clones. The Asterix, Atlantic and SMIC 148-A clones suffer interference of the type of propagation material in use efficiency and P response, while the SMINIA 793101-3 clone is P efficient in the use of nonresponsive in fresh mass production and tubers total dry mass, regardless of propagativa type of the plants. Furthermore, the clones were also evaluated with plants from tubers when grown in pots with soil as substrate in low and high P level (0.025 and 0.11g kg-1) in a greenhouse, we observed based on the total dry mass, the SMIC 148-A and SMINIA 793101- 3 clones are efficient in the use of P, while Atlantic and SMINIA 793101-3 are responsive to the increase of P.